Metal particles in mucus and hypertrophic tissue of the inferior nasal turbinates from the human upper respiratory tract - Čabanová, Kristina; Motyka, Oldřich; Čábalová, Lenka; Hrabovská, Kamila; Bielniková, Hana; Kuzníková, Ľubomíra; Dvořáčková, Jana; Zeleník, Karol; Komínek, Pavel; Kukutschová, Jana (Environmental science and pollution research international, 2020)
Mucosal surfaces are the first mechanical barrier preventing the entry of foreign particles into the organism. The study addresses the detection and analysis of metal-based solid particles in cytological mucus samples from the surface of human hypertrophic tissue in the inferior nasal turbinates in patients diagnosed with chronic rhinitis. Solid particles were characterized by scanning electron microscopy and Raman microspectroscopy; all the biological samples were also subjected to vibration magnetometry. Since the upper airways are the first part of the respiratory tract, which is exposed to inhaled particles, it can be assumed that inhaled particles may be partially deposited in this region. Scanning electron microscopy revealed the presence of metal-based solid particles/clusters in the majority of the analysed cytological mucus samples and also in hypertrophic tissues; in all groups, the particles were of submicron size. Raman microspectroscopy detected the presence of particles/clusters based on amorphous carbon, graphite, calcium carbonate, anatase and barite only in the hypertrophic tissue. The obtained results show that the composition of some of the solid particles (i.e. Ba, Zn, Fe and Ti) detected in the mucus from the surface of the hypertrophic tissues resembled the particles found in the hypertrophic tissue itself. It can be assumed that after the capture of the inhaled particles by the mucus, they penetrate into the deeper layers of tissue.
Keywords: Rhinitis; nosní skořepy; hlen; Scanning electron microscopy; Metals; rýma; Vibration magnetometry; Inhaled metal particles; lidé; Inflammatory tissue; kovy; Mucus; mikroskopie elektronová rastrovací; Microscopy, Electron, Scanning; Humans; Turbinates; Raman microspectroscopy